Personality dimensions and student’s participatory behavior in student organization - Marijana Markovikj; Eleonora Serafimovska (Institute for Sociological, Political and Juridical research, University SS. Cyril and Methodius, Skopje, Republic of Macedonia, 2018)
This text is based on the analysis of the data obtained from the wider research about the student’s participation in Student organization. During May, 2017 the field research among students at University of “Ss Cyril and Methodius” (UKIM) in Skopje was conducted. The total number of respondents was 669. Respondents were students from 1 till 5 year from almost all faculties which constitute UKIM. For the purpose of this research, two scales (Agreeableness and Conscientiousness) from the short version of IPIP NEO, (Five Factorial personality test) and Questionnaire were used. Agreeableness (A) personality dimension is a tendency to be compassionate and cooperative rather than suspicious and antagonistic toward others, and dimension Conscientiousness (C), is a tendency to be self-disciplined, to act dutifully. Both dimensions are relevant in institutionalized forms of participation (as student organization is). Questionnaire contains set of questions which were indicators for student’s participatory behavior. In this research participatory behavior has been defined as involvement and influence that students have in decision- making processes in student organization. The overall findings of this research pointed out that independent variables - personality dimensions (Agreeableness and Consciousness) cannot predict student’s participatory behavior in their student organization.
Keywords: Personality dimensions, Agreeableness, Consciousness Participatory behavior, Student organization